Female Labor Force Participation in Five Selected MENA Countries: An Age-Period-Cohort Analysis (Algeria, Egypt, Jordan, Palestine and Tunisia) - Moundir Lassassi; Aysit Tansel (Global Labor Organization (GLO), 2020)
This paper considers the female labor force participation (FLFP) behavior over the past decade in five MENA countries namely, Algeria, Egypt, Jordan, Palestine and Tunisia. Low FLFP rates in these countries, as it is in other MENA countries, are well documented. We conduct synthetic panel analysis using age-period-cohort (APC) methodology and decompose FLFP rates into age, period and cohort effects. We present our results with Hanoch-Honig/Deaton-Paxson normalization and maximum entropy estimation approaches to the APC methodology in order to observe robustness of our results. We first study the aggregate FLFP and note the differentials in age, period and cohort effects across the countries we consider. The analysis is carried also out by rural/urban regional differentiation, marital status and educational attainment. Implications of our results for possible government policies to increase FLFP rates are discussed.
Keywords: C23; C25; D1; J21; 330; Female labor force participation; synthetic panel analysis; life-cycle profiles; period effects; cohort effects; MENA countries